Using infographics to empower nursing students on integrating Ubuntu, HIV/AIDS and TB at a selected University, South Africa - M. N. Kgatla; T. I. Ramavhoya; M. M. Rasweswe; F. M. Mulaudzi (BMC Nursing)
Abstract Background Nursing students need to be equipped with specific knowledge on integrating Ubuntu, HIV/AIDS, and TB during their training to curb the pandemic in South Africa, specifically Limpopo Province. To stimulate nursing students’ critical thinking when caring for patients with HIV/AIDS and TB, the Students integrated Ubuntu principles to communicate care using creativity. Objectives To empower students to integrate Ubuntu when caring for patients living with HIV/AIDS and TB through infographics at a selected University in South Africa. Method A qualitative participatory study approach was followed. Data was collected by engaging 25-level 1st and 2nd year Nursing students to design infographics that integrate Ubuntu, HIV/AIDS, and TB during a workshop. The participants were purposively sampled based on their creative skills and understanding of the use of infographics. Textual data from discussions, visual data from infographics, and field notes were triangulated and subjected to thematic analysis. Measures to ensure trustworthiness and ethical issues were implemented. Results Different infographics on applying Ubuntu principles when caring for patients living with HIV/AIDS and TB were displayed and presented to the audience. Integrating Ubuntu principles, and caring for HIV/AIDS and TB through infographics were based on the knowledge and skills obtained during the workshop. The infographics and interpretations demonstrated that awareness of Ubuntu’s principles is closely connected to the quality care of patients living with HIV/AIDS and TB. Conclusion The infographics played an important role in understanding the integration of Ubuntu principles, HIV/AIDS, and TB. Contribution Students were empowered on the use of creativity to understand Ubuntu principles when caring for patients living with HIV/AIDS and TB.